2021
DOI: 10.1093/brain/awab354
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic reversal of Huntington’s disease by in vivo self-assembled siRNAs

Abstract: Huntington’s disease is an autosomal-dominant neurodegenerative disease caused by CAG expansion in exon 1 of the huntingtin (HTT) gene. Since mutant huntingtin (mHTT) protein is the root cause of Huntington’s disease, oligonucleotide-based therapeutic approaches using small interfering RNAs (siRNAs) and antisense oligonucleotides designed to specifically silence mHTT may be novel therapeutic strategies for Huntington’s disease. Unfortunately, the lack of an effective in vivo delivery system remains a major obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 65 publications
0
42
0
Order By: Relevance
“…The reaction mechanism of the probe is shown in Scheme 1. The probe structure has been verified by 1 HNMR, 13 CNM, and HRMS. The experimental data of 1 HNMR and HRMS show that the mechanism by which Gol-NTR recognizes NTR is consistent with our prediction.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The reaction mechanism of the probe is shown in Scheme 1. The probe structure has been verified by 1 HNMR, 13 CNM, and HRMS. The experimental data of 1 HNMR and HRMS show that the mechanism by which Gol-NTR recognizes NTR is consistent with our prediction.…”
mentioning
confidence: 90%
“…[9][10][11][12] Golgi dysfunction may be closely related to the occurrence of tumors. [13][14][15] An increasing number of studies have shown that the Golgi is the center that drives the survival and migration of cancer cells, so it is also important to monitor NTR in the cellular Golgi. 16 However, in the current field of fluorescent probes, there are few probes targeting the Golgi apparatus.…”
mentioning
confidence: 99%
“…In 2021, Chen et al proposed a strategy to stimulate host tissue to secrete therapeutic exosomes in vivo. 554 , 569 These exosomes with nucleic acid drugs and ligands directly migrate to the lesion for disease treatment. That is, there is no need to isolate, extract, purify, and modify exosomes and load drugs onto exosomes in vitro.…”
Section: Engineering Carriers Loaded With a Single Nucleic Acid Drug ...mentioning
confidence: 99%
“…This delivery method induced the downregulation of HMGB1 and decreased levels of tumor necrosis factor-α (TNF-α) and apoptosis, leading to reduced infarct volume [ 52 ]. Moreover, Zhang’s team established a self-assembly strategy of siRNAs in vivo with safety and effectivity and delivered mHTT-silencing siRNA to the cortex and striatum based on a rabies virus glycoprotein-tagged exosome-circulating system, ameliorating behavioral deficits in Huntington’s disease [ 57 ]. Meanwhile, the long-term influence of repeated administration on the liver function and exploration of the half-lives, distribution, and metabolism of exosomal siRNAs are conducive to the assessment of the safety and optimal dosage of exosomal RNAs delivery, which is the foundation of clinical translation [ 58 ].…”
Section: Therapeutic Prospects Of Exosomal Noncoding Rnas In the Trea...mentioning
confidence: 99%